Study of error control capability for the new moduli set \(2^2n+1+2^n-1, 2^2n+1-1, 2^n-1, 2^3n,2^3n+1-1\) - Modiri, Samira; Movaghar, Ali; Barati, Ali (Journal of Advanced Computer Science & Technology, 2012)
In this paper, a new 3-moduli set 22n+1+2n-1, 22n+1-1, 2n-1 with an efficient residue-to-binary converter using mixed radix conversion algorithm is presented. Moreover, by adding two redundant modulus 23n, 23n+1-1, a new moduli set in redundant residue number system is provided that can correct up to (2n+2) error bits. Simulation results of the error control algorithm's functionality with C++ programming language for 10'000 different error bits states show that the average percent of error detection capability using the proposed moduli set by setting n=2 is equal to 77.97%.